(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The methodology for conducting lessons and lectures consists of preparing a lesson as part of a training course, developing a system for quality control of educational material, as well as self-monitoring and monitoring the quality of teaching by the educational part of the educational institution. This topic is relevant today. A large number of teachers do not adhere to the norms and rules for preparing and conducting lessons. The material must be presented interestingly, competently and correctly. The purpose of this article is to analyze ways of preparing and conducting lessons in economic disciplines.